Health benefits of organic food [ effects of the environment - Givens, D. I. [ (D. Ian)] (CABI, 2008)
"Public concern over impacts of chemicals in plant and animal production on health and the environment has led to increased demand for organic produce, which is usually promoted and often perceived as containing fewer contaminants, more nutrients, and bg positive for the environment." "These benefits are difficult to quantify, and potential environmental impacts on such benefits have not been widely studied. This book addresses these key points, examining factors such as the role of certain nutrients in prevention and promotion of chronic disease, potential health benefits of bioactive compounds in plants, the prevalence of food-borne pesticides and pathogens and how both local and global environmental factors may affect any differences between organic and conventionally produced food." "This book is an essential resource for researchers and students in human health and nutrition, environmental science, agriculture and organic farming."--Jacket.